Preparation method and application of co-doped ferrous phosphate precursor material

By optimizing the preparation process of ferrous phosphate precursor and introducing metal ion co-doping, the problems of ferrous phosphate purity and morphology were solved, improving the electronic conductivity and lithium-ion diffusion rate of lithium iron phosphate, thus meeting the performance requirements of high-end lithium-ion batteries.

CN121449030APending Publication Date: 2026-02-03HUBEI XINGFA CHEM GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511754599.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-26
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

The existing ferrous phosphate precursor materials have insufficient purity, irregular morphology, and poor electronic conductivity and ion transport performance, which makes it impossible for lithium iron phosphate to meet the requirements of high-end lithium-ion batteries.

Method used

By optimizing the preparation process of ferrous phosphate precursor and introducing specific metal ions for co-doping, the morphological characteristics and charge transport properties of the material are controlled, and co-doped ferrous phosphate precursor materials are prepared.

Benefits of technology

It significantly improves the electronic conductivity and lithium-ion diffusion rate of lithium iron phosphate, enhances compaction density and rate performance, and is suitable for high-performance lithium-ion battery cathode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121449030A_ABST
    Figure CN121449030A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion battery positive electrode materials, and particularly discloses a preparation method and application of a co-doped ferrous phosphate precursor material.The preparation method comprises the steps that an antioxidant solution and a salt solution containing doped metal ions are added into a ferrite solution, and an iron source mixed solution is obtained; mixing and reacting a phosphorus source, an iron source and an alkaline solution to obtain blue ferrous phosphate slurry; and then filtering, washing, drying and crushing to obtain the doped ferrous phosphate precursor material. According to the invention, doping and morphology regulation and control are integrated in a single reaction system through a metal ion doping process, so that the preparation process is greatly simplified, and the compaction density and the rate capability of the prepared lithium iron phosphate positive electrode material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion batteries, specifically to a method for preparing a co-doped ferrous phosphate precursor material and its application. Background Technology

[0002] Lithium-ion batteries, with their advantages of high energy density, long cycle life, and environmental friendliness, have been widely used in electric vehicles, portable electronic devices, large-scale energy storage power stations, and other fields. Cathode materials, as a key component of lithium-ion batteries, directly determine the battery's electrochemical performance, safety performance, and cost control. Among them, LiFePO4 has become the mainstream cathode material for power batteries and energy storage batteries due to its high safety, long cycle life, and low cost. However, ferrous phosphate (Fe3(PO4)2), as a key precursor for preparing lithium iron phosphate (LiFePO4) cathode materials, has its purity, morphology, and intrinsic electrochemical properties directly determining the structure and performance of the subsequent calcination products. Therefore, optimizing the preparation process of ferrous phosphate precursors is crucial.

[0003] Currently, the main iron source used in the industrial preparation of lithium iron phosphate is iron phosphate. However, since the trivalent iron in iron phosphate needs to be reduced to divalent iron by a reducing agent during the reaction with the lithium source, it not only increases the amount of carbon source used and the difficulty of process control, but also easily leads to poor electronic conductivity and low lithium-ion diffusion rate in the final product due to incomplete reduction or uneven carbon residue. This makes it difficult to achieve breakthrough improvements in key indicators such as compaction density, discharge specific capacity and high rate performance of lithium iron phosphate, and cannot meet the urgent needs of high-end power batteries for high energy density and high power density.

[0004] Studies have shown that ferrous phosphate can be used as an iron source to prepare lithium iron phosphate. Since divalent iron does not require reduction, it can not only reduce the use of carbon reducing agents, lower production costs and carbon residue risks, but also simplify the reaction system and improve reaction uniformity. However, there are still problems with poor performance. On the one hand, ferrous phosphate prepared by conventional co-precipitation methods is prone to insufficient purity and high impurity content, and its microstructure is mostly irregular particles with wide particle size distribution and serious agglomeration. On the other hand, the unmodified pure ferrous phosphate precursor itself has poor electronic conductivity and ion transport performance, which directly affects the electrochemical kinetic performance of subsequent lithium iron phosphate products, resulting in its overall performance still not being able to fully meet the needs of high-end application scenarios. For example, patent CN118702079A discloses a method for preparing ferrous phosphate octahydrate using ferrous sulfate. This method removes impurities such as Mg and Mn that are easily precipitated in the high pH system through a two-step process. However, the operation process is cumbersome, and oxidation is prone to occur during the filtration process. The sample oxidation degree is high, and it is impossible to obtain ferrous phosphate octahydrate with high crystallinity and high purity.

[0005] In view of this, the present invention optimizes the preparation process of ferrous phosphate precursor and introduces metal ion doping to regulate the morphology characteristics of the precursor, thereby achieving synergistic optimization of lattice expansion and charge transport of ferrous phosphate material and improving compaction density and rate performance. Summary of the Invention

[0006] To address the problems mentioned above, the main objective of this invention is to provide a method for preparing and applying a co-doped ferrous phosphate precursor material. This invention significantly improves the electronic conductivity and lithium-ion diffusion rate of lithium iron phosphate by optimizing the preparation process of the ferrous phosphate precursor material and doping it with a specific amount of metal ions.

[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a co-doped ferrous phosphate precursor material includes the following steps: (1) Add antioxidant solution and metal salt to ferrous salt solution, mix thoroughly to obtain iron source mixed solution; (2) Place the phosphorus source solution in the reaction vessel, heat it under the protection of inert gas, then add the iron source mixed solution and alkaline solution, stir continuously until the mixture is uniform, adjust the pH to weakly acidic, continue stirring and aging to obtain blue ferrous phosphate slurry; (3) The ferrous phosphate slurry is filtered, washed, dried and crushed to obtain the doped ferrous phosphate precursor material.

[0008] Preferably, the ferrous salt solution is prepared by dissolving ferrous salt in deoxygenated deionized water, wherein the deionized water is deoxygenated to remove dissolved oxygen and prevent ferrous ions from being oxidized.

[0009] Preferably, the ferrous salt is at least one of ferrous sulfate, ferrous chloride, and ferrous nitrate; the antioxidant is at least one of sodium sulfite, sodium thiosulfate, and water-soluble vitamin E, preferably sodium sulfite.

[0010] Preferably, the antioxidant in the antioxidant solution has a mass fraction of 0.05% to 0.2%.

[0011] Preferably, the metal ion of the metal salt in step (1) is Mg. 2+ Al 3+ Ti 4+ V 5+ Bi 3+ or Zn 2+ At least two of them; the mass is 500~6000ppm.

[0012] Preferably, the phosphorus source solution is obtained by dissolving phosphate in deionized water.

[0013] Preferably, the phosphorus source is at least one selected from phosphoric acid, phosphate compound fertilizer, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, potassium monohydrogen phosphate, potassium dihydrogen phosphate, and potassium phosphate.

[0014] Preferably, the reaction temperature in step (2) is 50~80℃; the alkaline solution is at least one of sodium hydroxide solution, potassium hydroxide solution and ammonia water; the pH value is 4.0~6.5; and the aging time is 2-8h. In step (2), the molar ratio of iron to phosphorus in the iron source and phosphorus source is (1.42~1.52):1.

[0015] Preferably, the drying method in step (3) is vacuum drying or drying under an inert atmosphere; the drying temperature is 50~100℃ and the drying time is 12~24h.

[0016] The second aspect of this invention provides the application of the ferrous phosphate precursor material obtained by the preparation method in lithium iron phosphate cathode materials.

[0017] Preferably, the application specifically involves: grinding, spraying, calcining, and pulverizing the ferrous phosphate precursor material with a lithium source and a carbon source to obtain a lithium iron phosphate cathode material.

[0018] Preferably, the lithium source is at least one selected from lithium carbonate, lithium hydroxide, lithium acetate, and lithium phosphate; and the carbon source is at least one selected from glucose, sucrose, and polyethylene glycol.

[0019] Preferably, the calcination treatment is carried out in an inert gas at a temperature of 600-800°C for 4-10 hours; the inert gas is at least one of nitrogen or argon, more preferably nitrogen.

[0020] Preferably, the molar ratio of iron, carbon, and lithium in the precursor material, carbon source, and lithium source is 1:(0.2~0.5):(1.01~1.05).

[0021] This invention enables lithium iron phosphate cathode materials to exhibit significant advantages in terms of compaction density, discharge capacity, and rate performance through metal ion co-doping. It solves the problems of uneven particle morphology, excessive large particles, low compaction density, and insufficient discharge capacity of undoped lithium iron phosphate, and is suitable for the preparation of high-performance lithium-ion battery cathode materials.

[0022] The beneficial effects of this invention are as follows: 1. This invention prepares lithium iron phosphate cathode materials through metal ion co-doping. On the one hand, it can control crystal growth, resulting in regular particle morphology, uniform particle size, and narrow particle size distribution (0.2-0.6 μm), significantly improving the material's compaction density (2.57-2.62 g / cm³). 3On the other hand, undergoing two sintering processes can improve the solid solubility between the dopant elements and the lithium iron phosphate bulk, allowing them to be more effectively embedded in the lithium iron phosphate lattice. Furthermore, co-doping can significantly reduce the lithium-ion migration barrier, thereby optimizing the crystal structure and ion and electron transport performance. This results in lithium iron phosphate having a high discharge specific capacity at different rates such as 0.1C, 0.5C, and 1C, with stable rate performance and smaller capacity decay under long-cycle testing.

[0023] 2. This invention integrates doping and morphology control into a single reaction system through a one-step in-situ doping process, which greatly simplifies the preparation process.

[0024] 3. The reaction process of this invention is mild, the production process is simple, the reaction conditions are easy to control, the production cost is low, and it is easy to carry out large-scale production and application. Attached Figure Description

[0025] The present invention will be further described below with reference to the accompanying drawings: Figure 1 This is a SEM image of the ferrous phosphate precursor material prepared in Example 1 of this invention; Figure 2 This is the XRD pattern of the ferrous phosphate precursor material prepared in Example 1 of this invention; Figure 3 This is a SEM image of the lithium iron phosphate cathode material prepared in Example 1 of this invention; Figure 4 This is a SEM image of the lithium iron phosphate cathode material prepared in Comparative Example 3 of this invention; Figure 5 This is a graph showing the long-cycle performance of the lithium iron phosphate cathode materials prepared in Example 1 and Comparative Example 3 of the present invention at a current density of 0.2C. Detailed Implementation

[0026] To better understand the present invention, the following embodiments further illustrate the content of the present invention, but the content of the present invention is not limited to the following embodiments.

[0027] Example 1: (1) Dissolve 2 mol of ferrous sulfate in deoxygenated deionized water to obtain a ferrous solution with a concentration of 1.0 mol / L. Add 0.1% sodium sulfite solution, 4000 ppm titanium oxysulfate and 2500 ppm magnesium sulfate, mix thoroughly to obtain a ferrous mixed solution. (2) Dissolve 1.37 mol of monoammonium phosphate in deoxygenated deionized water to obtain a phosphorus source solution with a concentration of 1.0 mol / L; (3) Place the phosphorus source solution in the reactor and heat it to 50°C under nitrogen protection. Then add the ferrous mixed solution and 10% dilute ammonia water. Set the speed to 350 rpm and stir continuously until the mixture is uniform. Adjust the pH to 5.5 and continue stirring and aging for 4 hours to obtain blue ferrous phosphate slurry. (4) The ferrous phosphate slurry was poured into a stainless steel microporous membrane filter for filtration, and washed with ultrapure water. The filter cake was then placed in a vacuum oven at 70°C for 12 hours and finally crushed with a pulverizer to obtain the co-doped ferrous phosphate precursor material. (5) According to the molar ratio of iron element: lithium element: carbon element of 1:1.03:0.4, the above precursor material is weighed and sand-milled with lithium source and carbon source. The resulting yellow material is calcined in an atmosphere furnace at 800°C for 9 hours under nitrogen atmosphere. After cooling to room temperature, it is pulverized to obtain lithium iron phosphate cathode material. The particle size D50 of black material is about 0.8-1.2μm.

[0028] SEM images of the co-doped ferrous phosphate precursor material are shown below. Figure 1 As shown. By Figure 1 It can be seen that the ferrous phosphate prepared in this embodiment is mostly a uniformly thick lamellar structure, which is stacked on top of each other, and the D50 particle size is 8~13μm.

[0029] The XRD pattern of the co-doped ferrous phosphate precursor material is as follows: Figure 2 As shown. By Figure 2 It can be seen that the ferrous phosphate material is monoclinic, and sharp characteristic diffraction peaks of Fe3(PO4)2·8H2O appear at 2θ=13.15°. All diffraction peaks are basically consistent with the standard card PDF#83-2453, indicating that the doping of Ti and Mg elements has little effect on the crystal structure of Fe3(PO4)2·8H2O.

[0030] SEM images of the obtained lithium iron phosphate cathode material are shown below. Figure 3 As shown. By Figure 3 It can be seen that the lithium iron phosphate prepared by the method of the present invention is mainly composed of small particles, with medium and large particles in a graded manner. The particle size is concentrated in 0.2~0.6μm, and the sphericity is high, with less agglomeration and adhesion between particles.

[0031] The ICP results of the obtained lithium iron phosphate cathode material are shown in Table 2. As can be seen from Table 2, the actual titanium doping content in the lithium iron phosphate cathode material prepared by the method of the present invention is 3869 ppm and the magnesium doping content is 2362 ppm, indicating a low doping loss rate. After two sintering processes at the precursor end, the solid solubility between the dopant element and the lithium iron phosphate bulk can be improved, enabling it to be effectively embedded into the lithium iron phosphate lattice.

[0032] The long-cycle test results of the obtained lithium iron phosphate cathode material at a current density of 0.2C are as follows: Figure 5 As shown. By Figure 5 It can be seen that the lithium iron phosphate cathode material prepared by the method of the present invention has higher and more stable discharge specific capacity and longer cycle life.

[0033] Example 2: Ferrous phosphate precursor material was prepared according to the method of Example 1, except that: magnesium sulfate in step (1) was replaced with zinc chloride, and the amount was 2000 ppm.

[0034] Example 3: The ferrous phosphate precursor material was prepared according to the method of Example 1, except that the titanium oxysulfate in step (1) was replaced with vanadium oxysulfate, and the amount was 2800 ppm.

[0035] Example 4: Ferrous phosphate precursor material was prepared according to the method of Example 1, except that: magnesium sulfate in step (1) was replaced with bismuth nitrate, and the amount was 2000 ppm.

[0036] Example 5: Ferrous phosphate precursor material was prepared according to the method of Example 1, except that: magnesium sulfate in step (1) was replaced with vanadium oxysulfate, and the amount was 3000 ppm.

[0037] Comparative Example 1: The ferrous phosphate precursor material was prepared according to the method of Example 1, except that only titanium oxysulfate was added in step (1).

[0038] Comparative Example 2: Ferrous phosphate precursor material was prepared according to the method of Example 1, except that only magnesium sulfate was added in step (1).

[0039] Comparative Example 3: The ferrous phosphate precursor material was prepared according to the method of Example 1, except that no metal salt was added in step (1).

[0040] The SEM image of the lithium iron phosphate cathode material prepared in this comparative example is shown below. Figure 4 As shown. By Figure 4 It can be seen that the particle size of lithium iron phosphate is concentrated in the range of 0.4~0.8μm, the particle shape is different, and the adhesion phenomenon is serious, which leads to a significant reduction in compaction density.

[0041] The long-cycle test results of the lithium iron phosphate cathode material prepared in this comparative example at a current density of 0.2C are as follows: Figure 5 As shown. By Figure 5 It can be seen that, due to the presence of many broken particles, Li... +Continuous deintercalation causes cracking, and the intensified side reactions with the electrolyte lead to irreversible capacity loss, thus significantly reducing the battery's cycle life and discharge specific capacity at different rates.

[0042] Comparative Example 4: The ferrous phosphate precursor material was prepared according to the method of Example 1, except that in step (1), the titanium oxysulfate was 2500 ppm and the magnesium sulfate was 2500 ppm.

[0043] Comparative Example 5: The ferrous phosphate precursor material was prepared according to the method of Example 1, except that in step (1), the titanium oxysulfate was 5000 ppm and the magnesium sulfate was 2000 ppm.

[0044] Comparative Example 6: The ferrous phosphate precursor material was prepared according to the method in Example 1, except that a back-end doping method was used to prepare the lithium iron phosphate cathode material. The specific experimental procedures are as follows: (1) Dissolve 2 mol of ferrous sulfate in deoxygenated deionized water to obtain a ferrous solution with a concentration of 1.0 mol / L. Add ascorbic acid with a mass fraction of 1‰ and mix thoroughly to obtain a ferrous mixed solution. (2) Dissolve 1.37 mol of monoammonium phosphate in deoxygenated deionized water to obtain a phosphorus source solution with a concentration of 1.0 mol / L; (3) Place the phosphorus source solution in the reactor and heat it to 50°C under nitrogen protection. Then add the ferrous mixed solution and 10% dilute ammonia water. Set the speed to 350 rpm and stir continuously until the mixture is uniform. Adjust the pH to 5.5 and continue stirring and aging for 4 hours to obtain blue ferrous phosphate slurry. (4) The ferrous phosphate slurry was poured into a stainless steel microporous membrane filter for filtration, and washed with ultrapure water. The filter cake was then placed in a vacuum oven at 70°C for 12 hours and finally crushed with a pulverizer to obtain the co-doped ferrous phosphate precursor material. (5) According to the molar ratio of iron element: lithium element: carbon element of 1:1.03:0.4, 4000ppm of titanium oxysulfate and 2500ppm of magnesium sulfate were weighed and ground with the above-mentioned precursor materials, lithium source and carbon source, and sprayed. The resulting yellow material was calcined in an atmosphere furnace at 800℃ for 9h under nitrogen atmosphere. After cooling to room temperature, it was pulverized to obtain lithium iron phosphate cathode material. The particle size D50 of the black material was controlled at about 0.8-1.2μm.

[0045] The lithium iron phosphate cathode materials prepared in the above examples and comparative examples were assembled into lithium-ion batteries, and rate performance tests were conducted at current densities of 0.1C, 0.5C, and 1C. The test results are shown in Table 1.

[0046] Table 1

[0047] As shown in Table 1, the compaction density and discharge specific capacity of the examples are significantly higher than those of the comparative examples, indicating that bimetallic co-doping can effectively suppress particle agglomeration, promote uniform grain growth, optimize particle size distribution, and reduce the lithium-ion migration barrier, thereby improving the particle packing density, rate performance, and cycle stability of lithium iron phosphate. Among them, Example 1 has the best performance.

[0048] Compared with Comparative Examples 4-5, Example 1 shows that both excessively low and excessively high metal doping can lead to performance degradation, indicating that optimal performance can only be achieved within a suitable doping concentration range. Compared with Comparative Example 6, Example 1 uses front-end co-doping, which helps the dopant elements achieve atomic-level uniform distribution in the crystal lattice and form a stable solid solution structure. In contrast, Comparative Example 6 uses back-end doping, which can only achieve surface adhesion or local coating and is difficult to effectively enter the crystal lattice, resulting in a significant decrease in electrochemical performance.

[0049] To further investigate the difference in material purity between Example 1 and Comparative Example 3, the prepared lithium iron phosphate materials were subjected to impurity element detection, and the results are shown in Table 2.

[0050] Table 2 Elemental Analysis (mg / kg)

[0051] As shown in Table 2, the content of various impurity elements in Example 1 is significantly lower than that in Comparative Example 3. This indicates that the use of Ti and Mg bimetallic co-doping not only optimizes the crystal structure and particle morphology of the material, but also significantly reduces grain boundary defects and porosity by promoting uniform grain growth and structural densification, effectively suppressing the adsorption and enrichment of impurity elements, and improving the purity and electrochemical stability of the material. In contrast, Comparative Example 3, due to the lack of doping control, has more crystal structure defects and a larger specific surface area, making it easier for impurities to accumulate, thus affecting the purity and long-term cycling stability of the material.

[0052] The results above demonstrate that front-end co-doping combined with appropriate bimetallic doping can significantly improve the crystallinity, particle uniformity, and compaction density of lithium iron phosphate precursors, thereby achieving excellent electrochemical performance. In contrast, single doping, no doping, or back-end doping all lead to a decrease in performance, indicating that the appropriate doping method and precisely controlled doping amount jointly determine the microstructure and macroscopic performance of lithium iron phosphate cathode materials.

[0053] The above embodiments are merely preferred technical solutions of the present invention and should not be considered as limitations on the present invention. The scope of protection of the present invention should be limited to the technical solutions described in the claims, including equivalent substitutions of the technical features described in the claims. That is, equivalent substitutions and improvements within this scope are also within the scope of protection of the present invention.

Claims

1. A method for preparing a co-doped ferrous phosphate precursor material, characterized in that, Includes the following steps: (1) Add antioxidant solution and metal salt to ferrous salt solution, mix thoroughly to obtain iron source mixed solution; (2) Place the phosphorus source solution in the reaction vessel, heat it under the protection of inert gas, then add the iron source mixed solution and alkaline solution, stir continuously until the mixture is uniform, adjust the pH to weakly acidic, continue stirring and aging to obtain blue ferrous phosphate slurry; (3) The ferrous phosphate slurry is filtered, washed, dried and crushed to obtain the doped ferrous phosphate precursor material.

2. The preparation method according to claim 1, characterized in that, The antioxidant solution contains 0.05%-0.2% by mass of antioxidant.

3. The preparation method according to claim 1, characterized in that, In step (1), the metal ion of the metal salt is Mg. 2+ Al 3+ Ti 4+ V 5+ Bi 3+ or Zn 2+ At least two of them; the mass is 500~6000ppm.

4. The preparation method according to claim 1, characterized in that, In step (2), the molar ratio of iron to phosphorus in the iron source and phosphorus source is (1.42~1.52):

1.

5. The preparation method according to claim 1, characterized in that, In step (2), the reaction temperature is 50~80℃ and the aging time is 2-8h.

6. The preparation method according to claim 1, characterized in that, In step (3), the drying method is vacuum drying or drying under an inert atmosphere; the drying temperature is 50~100℃, and the drying time is 12~24h.

7. The application of the ferrous phosphate precursor material obtained by the preparation method according to any one of claims 1 to 6 in lithium iron phosphate electrode materials.

8. The application according to claim 7, characterized in that, Lithium iron phosphate cathode material is prepared by sand milling, spraying, calcining and pulverizing ferrous phosphate precursor material with lithium source and carbon source.

9. The application according to claim 8, characterized in that, The calcination process is carried out in an inert gas, wherein the inert gas is at least one of nitrogen or argon; the calcination temperature is 600~800℃ and the calcination time is 4~10h.

10. The application according to claim 8, characterized in that, The molar ratio of iron, carbon, and lithium in the iron source, carbon source, and lithium source is 1:(0.2~0.5):(1.01~1.05).

Citation Information

Patent Citations

  • Ferrous phosphate powders, lithium iron phosphate powders for li-ion battery and methods for manufacturing same

    CN104218215A

  • Carbon-coated multi-element doped pyrophosphate ferric sodium phosphate and preparation method thereof

    CN118387852A

  • Carbon-coated titanium-doped lithium iron phosphate positive electrode material and preparation method thereof

    CN119674025A